Application of online microdialysis coupled with liquid chromatography-tandem mass spectrometry method in assessing neuroprotective effect of Rhizoma coptidis on diabetic rats. Issue 1 (7th October 2014) - Wang, Qianqian; Zhang, Jing; Pi, Zifeng; Zheng, Zhong; Xing, Junpeng; Song, Fengrui; Shu Liu,; Liu, Zhiqiang
Abstract : An online microdialysis coupled with LC-MS/MS method is applied for rapid, sensitive and direct in vivo analysis. Abstract : Monitoring the in vivo dynamics of neurochemicals is very important for studies on learning and memory impairment. However, drawbacks in conventional sampling and off-line analysis methods require the employment of a more satisfying system. We present an online microdialysis coupled with liquid chromatography-tandem mass spectrometry method (LC-MS/MS) to determine eight neurochemicals simultaneously, including glutamate, aspartic acid, γ-aminobutyric acid, serine, taurine and acetylcholine, as well as dopamine and serotonin. A self-assembled automated injector with a high-pressure-resisting six-port valve was utilized to control the switch of the two states between loading and injection, which potentially simplified the sample preparation procedures and avoided the restrictions offered by small sample volume. Good linearity ( R 2 > 0.997) was observed in each analyte dynamic range. The inter-day and intra-day precisions (RSD) were <15%, and the accuracy (RE) was from −13.84% to 11.16%. The overall matrix effect was within an acceptable range, from 87.79% to 111.71%. Morris water maze (MWM) test was performed to evaluate the differences of cognitive abilities among normal control, diabetes mellitus (DM) model and Rhizoma coptidis ( R. coptidis )-treated DM group rats. Moreover, the developed method was applied for the further exploration of the R. coptidis efficacies on the eight analytes changes in the hippocampus of diabetic rats with mild cognitive impairment. It was found that an improvement in neurochemicals imbalance was observed in diabetic rats after treatment with R. coptidis . In conclusion, the developed online analysis method is selective, sensitive and accurate, which is suitable for in vivo neurochemicals monitoring and could be extended to pharmacology studies.